2017
DOI: 10.3390/w10010017
|View full text |Cite
|
Sign up to set email alerts
|

Non-Point Source Nitrogen and Phosphorus Assessment and Management Plan with an Improved Method in Data-Poor Regions

Abstract: Abstract:To enhance the quantitative simulation and integrated assessment of non-point source (NPS) pollution in plateau lakes in data-poor regions, a simple and practical NPS assessment method is developed by combining the improved export coefficient model (ECM) and the revised universal soil loss equation (RUSLE). This method is evaluated via application to the Chenghai Lake watershed (Yunnan Province, China), which contains a typical plateau lake. The estimated results reflect the actual situation within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
0
12
0
6
Order By: Relevance
“…The values can be estimated using the export coefficient model (ECM). The adsorbed NPS pollutants are mainly controlled by soil erosion and they can be estimated using the Revised Universal Soil Loss Equation (RUSLE) [12].…”
Section: Estimation Of Nps Pollutants Amountsmentioning
confidence: 99%
See 3 more Smart Citations
“…The values can be estimated using the export coefficient model (ECM). The adsorbed NPS pollutants are mainly controlled by soil erosion and they can be estimated using the Revised Universal Soil Loss Equation (RUSLE) [12].…”
Section: Estimation Of Nps Pollutants Amountsmentioning
confidence: 99%
“…Simulation, estimation, and quantitative measurement are the basis for effective treatment of NPS pollution [11]. Many studies have shown that traditional terminal management technologies for point source pollution control is hard to effectively apply to NPS source pollution control [12]. With the rapid development of science and methodology, particularly the wide application of remote sensing, Global Positioning System, and Geographic Information System (3S) technologies, a large amount of NPS pollution estimation models have been introduced, which could be separated into physical models and empirical models.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The world is facing more and more serious water pollution problems, and non-point source (NPS) pollution has gradually become the most significant factor [1]. Both anthropogenic factors and ecological factors have a major impact on NPS pollution.…”
Section: Introductionmentioning
confidence: 99%